2007
DOI: 10.1007/s00192-007-0491-9
|View full text |Cite
|
Sign up to set email alerts
|

Levator avulsion and grading of pelvic floor muscle strength

Abstract: In a retrospective study investigating the relationship between levator avulsion and clinical grading of levator ani muscle strength, we analyzed the 3D/4D translabial ultrasound and digital assessment data of 1,112 women seen in a tertiary Urogynecological clinic. Levator avulsion was diagnosed whenever the examiner was unable to palpate the insertion of the pubovisceral muscle on the inferior pubic ramus and/or whenever a discontinuity between bone and muscle was detected on ultrasound. For clinical grading … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
108
1
10

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(126 citation statements)
references
References 13 publications
7
108
1
10
Order By: Relevance
“…Previous studies in prolapse patients have revealed a reduced PFMS in women with LAM avulsion. 11,12 Moreover, supervised pelvic floor muscle training to increase PFMS in women with POP can improve severity of prolapse and reduce prolapse symptoms. 44 Postnatal hiatus area was significantly larger in women with major LAM avulsion (except at rest), compared with women without LAM avulsion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies in prolapse patients have revealed a reduced PFMS in women with LAM avulsion. 11,12 Moreover, supervised pelvic floor muscle training to increase PFMS in women with POP can improve severity of prolapse and reduce prolapse symptoms. 44 Postnatal hiatus area was significantly larger in women with major LAM avulsion (except at rest), compared with women without LAM avulsion.…”
Section: Discussionmentioning
confidence: 99%
“…7 A 2.4-2.9 fold increase of anatomical cystocele recurrence has been shown in women with LAM avulsion, although not all women were symptomatic. 8,9 In addition to POP, 5,6,10 women with LAM avulsion are at risk of a reduction in pelvic floor muscle strength (PFMS) [11][12][13] and an increased vaginal hiatus. [14][15][16] Although the literature is ambiguous, these anatomical changes may lead to symptoms of pelvic floor dysfunction (PFD).…”
Section: Introductionmentioning
confidence: 99%
“…It is clearly related to vaginal childbirth [3,4], with Forceps delivery, length of second stage and foetal size as likely risk factors [5,6]. Such trauma is associated with abnormal muscle biometry and function as well as female pelvic organ prolapse [1,2,[7][8][9]. Avulsion increases the area of the levator hiatus [5,7], the largest potential hernial portal in the abdominal envelope.…”
Section: Introductionmentioning
confidence: 99%
“…MRI can show the axial plane, but it is expensive, not readily available and time consuming. Moreover, due to the physical properties of the device, required maneuvers cannot always be performed by the patient during dynamic MRI [44].…”
Section: Urogynecologymentioning
confidence: 99%